Correction to: Motor impulsivity and delay intolerance are elicited in a dose-dependent manner with a dopaminergic agonist in parkinsonian rats - Jiménez-Urbieta, Haritz; Gago, Belén; Quiroga-Varela, Ana; Rodríguez-Chinchilla, Tatiana; Merino-Galán, Leyre; Delgado-Alvarado, Manuel; Navalpotro-Gómez, Irene; Belloso-Iguerategui, Arantzazu; Marin, Concepció; Rodríguez-Oroz, María C. (Psychopharmacology, 2020)
In the original version of this article, the Figure 3 was published in an incorrect format, even though the data and the related information in the text are correct.In the original version of this article, the Figure 3 was published in an incorrect format, even though the data and the related information in the text are correct.